Pharmacological aspects of the most important organelles of the cell in the exchange of substances in the body - Isroilov Xikmatullo Adxamjon o’g’li (Periodica Journal, 2022)
In this paper, quantitative changes in lipid content in the liver mitochondria were measured at different times after heliotrin was administered to rats to determine the pathogenetic significance of hepatitis in the liver.
Keywords: Mitochondria; lipid; hepatitis; membrane